Study of cooperation in agribusiness as a socio-economic phenomenon - Horbonos, Fedir; Pavlenchyk, Nataliya; Pavlenchyk, Anatolii; Skrynkovskyy, Ruslan (Technology audit and production reserves, 2017)
The object of research is the processes of development of cooperative relationships in agribusiness, which form the basis of an economic phenomenon, the essence of which is cooperation, as well as the formation and improvement of its organizational and legal forms. For today, the existence of cooperative formations is justified by centuries of practice, and its objectivity is beyond doubt. However, it is important to streamline the methodological foundations of research, which will ensure the formation and implementation of cooperative policies in the agro-industrial complex in order to improve the efficiency of its functioning. This calls for a deep theoretical rethinking of the essence and significance of cooperation. In the course of research, economic phenomena are viewed not in isolation and from specific historical circumstances, but comprehensively, taking into account specific economic conditions and the real state of the economic, political and social situation in the country. As a result of research, it is justified that «agribusiness» is such sphere of entrepreneurial activity, the effective development of which is capable of ensuring the welfare of the population, creating conditions for the successful development of other industries. This will contribute to raising the level of economic, and therefore political, security of Ukraine. For the development of cooperation, favorable conditions are necessary, the influence of which on the development level of cooperative relations is expressed in the actions of specific factors. These factors can be systematized, as production, organizational-base, stimulating-legal and stabilizing. In the course of research, it is determined that cooperation in its content is an economic phenomenon, the essence of which is economic relations between partners, on their cooperation for achieving a common goal. This methodological approach to understanding cooperation is important from a practical point of view, since it assumes the creation of an infrastructure, as an indispensable condition for the further successful development of this phenomenon. It is established that the cooperative is a form of cooperation and its organizational structure of an entrepreneurial type, it is created and functions on the basis of cooperative principles that are carriers and regulators of its internal and external relations.